2010
DOI: 10.1097/mbc.0b013e32833b643b
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant activity of a dermatan sulfate from the skin of the shark Scyliorhinus canicula

Abstract: A dermatan sulfate isolated from the shark Scyliorhinus canicula skin by enzymatic digestion followed by purification with anion exchange chromatography was identified by chondroitinase and nitrous acid treatment and partially characterized by Fourier-transform infrared spectroscopy. Dermatan sulfate was the major glycosaminoglycan and represented 75% of the polysaccharide fraction in the sharkskin. This dermatan sulfate had a 38.6 kDa average molecular weight and 23% sulfate content. The anticoagulant action … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 41 publications
3
28
0
Order By: Relevance
“…It was showed that dermatan sulfate exhibited a high anticoagulant activity (Ben Mansour et al 2009a, b , 2010. Similar activity of a dermatan sulfate from the skin of the shark Scyliorhinus canicula was also reported by Dhahri et al ( 2010 ). The substance of the shark origin showed anticoagulant effect that was higher than that isolated from pork.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…It was showed that dermatan sulfate exhibited a high anticoagulant activity (Ben Mansour et al 2009a, b , 2010. Similar activity of a dermatan sulfate from the skin of the shark Scyliorhinus canicula was also reported by Dhahri et al ( 2010 ). The substance of the shark origin showed anticoagulant effect that was higher than that isolated from pork.…”
Section: Resultssupporting
confidence: 73%
“…Proteoglycans (Tingbø et al 2012 ) as well as glycosaminoglycans (GAGs) like chondroitin sulfate (Hashiguchi et al 2011 ), dermatan sulfate (Chatziioannidis et al 1999 ;Sakai et al 2003 ;Dhahri et al 2010 ), aggrecan (Kakizaki et al 2011 ) and hyaluronan (Pfeiler et al 2002 ) has been also isolated from marine vertebrates, mostly from fi sh.…”
Section: Resultsmentioning
confidence: 98%
“…It is believed that these therapeutic effects are due to DS-IEL 30 binding to the vessel wall and subsequently preventing platelet binding and not through direct anticoagulant properties. Dermatan sulfate from porcine origin (which is the type used for EC-SEAL synthesis) has been shown to have very minimal anticoagulant properties depending on the concentration [54]. By measuring aPTT of whole blood that had been incubated with varying concentrations of both heparin and DS-IEL 30 , we have confirmed the minimal effect of DS-IEL 30 on clotting time (Figure 11).…”
Section: Discussionmentioning
confidence: 58%
“…In previous studies, we isolated and characterized a DS from the skin of the Scyliorhinus canicula shark, a nonmammalian marine product, which decreases the risk of pathogenic contamination . Furthermore, we demonstrated that soluble DS exhibited an antithrombin activity mediated by heparin cofactor II, a serine protease inhibitor . We have also shown that immobilization of DS on PET surfaces decreased fibrinogen adsorption while it increased albumin adsorption on the PET surfaces, enhanced both in vitro endothelial cell proliferation and the tissue biocompatibility in subcutaneous implantation in a rat model …”
Section: Introductionmentioning
confidence: 89%
“…DS was obtained by papain digestion followed by cetyltrimethylammonium bromide (CTAB) and ethanol precipitation then dialyzed against deionized water, and a diethylaminoethyl (DEAE)‐cellulose anion‐exchange chromatography step was performed to separate DS from hyaluronic acid. The DS fractions were then pooled and lyophilized …”
Section: Methodsmentioning
confidence: 99%